Digitalisasi Penyiaran Radio di Mitra FM Purwokerto - Pamungkas, Anggit; Halwati, Umi (Program Studi Komunikasi Penyiaran Islam Universitas Sains Al-Qur'an Jawa Tengah di Wonosobo, 2023)
Broadcast digitization is the technical term for making the transition from analog to digital media formats. The digitization of broadcasting is critical because modern life's demands for perfection, brevity, and speed have rendered analog obsolete. The rise of digital television is predicted to provide a larger audience for broadcasting institutions. The principle of independent production and ownership is emphasized in this digital radio. Due to the explosive growth of the internet, competition among radio stations is fierce. Managers in the broadcast radio industry need to be more resourceful and original if they want to increase the size of their audience. Because if you can't compete, radio will die because you can't compete with the reach of online news outlets. Radio needs flexibility to develop with other media, especially the internet. Without competition, the radio industry would stagnate. Radio station management needs to be continuously improved so that radio broadcasts can survive facing competition from other social media. The method in this research is qualitative. Data collection methods namely Observation, Interview, and Documentation. Mitra FM Purwokerto does the same to maintain and increase their audience. Mitra FM Purwokerto is fully committed to making the most of all available social media platforms. Purwokerto Mitra FM radio station makes extensive use of platforms such as Facebook, Instagram and YouTube. Live streaming on social media platforms such as Instagram and Facebook facilitates communication from Mitra FM Purwokerto to listeners.